An inhibitor of the protein kinases TBK1/IKKε improves obesity-related metabolic dysfunctions - Reilly, Shannon M. (2013)
Emerging evidence suggests that inflammation provides a link between obesity and insulin resistance. The noncanonical IκB kinases IKKε and TANK-binding kinase 1 (TBK1) are induced in liver and fat after high fat diet by NF-κB activation, and in turn initiate a program of counter-inflammation that preserves energy storage. Here, we report the discovery of a small molecule inhibitor of these kinases called amlexanox. Treatment of obese mice with amlexanox elevates energy expenditure through increased thermogenesis, producing weight loss, improved insulin sensitivity and decreased steatosis in obese mice. Because of its record of safety in patients, amlexanox may be an interesting candidate for clinical evaluation in the treatment of obesity and related disorders.